PENGARUH UKURAN PERUSAHAAN DAN PROFITABILITAS PADA PRAKTIK PERATAAN LABA DENGAN JENIS INDUSTRI SEBAGAI VARIABEL PEMODERASI DI BURSA EFEK INDONESIA - dewi, yustiari; Sujana, I Ketut (E-Jurnal Akuntansi, 2014)
1024x768 Earnings management strategies most enduring over time is income smoothing. Income information from the financial statements to be a reference for management to perform income smoothing practices. The purpose of the study was to determine the effect of firm size and profitability on income smoothing practices by industry type as a moderating variable. 56 samples selected by purposive sampling method. Hypothesis testing using logistic regression analysis associated with the dependent variable is a dummy variable.The results of the analysis are firm size and profitability of the practice of income smoothing effect, while the industry is not able to moderate the type of firm size and profitability of the practice of income smoothing. Normal 0 false false false EN-US X-NONE X-NONE
Keywords: income smoothing, firm size, profitability and industry types.